(untitled) (Islamic Sciences Journal, 2023)
Economy is the backbone of life because of its major role in life’s survival and permanence. Throughout history, man has dealt with money in an unorganized manner that led to attempts of robbery, looting and invasion that most civilizations in history, ancient and modern, went through. in the permanence of society. In the third century of Hijrah, the genius of Al-Ya’qubi was a researcher in history and news of countries, and he gave Tanqeeb his right to travel in countries east and west, he entered Persia and extended his stay in Armenia, he entered India and wandered in the Levant, Morocco and Andalusia, he asked the people of the cities about them, about them, their customs, and their settlement And their governments, and about the distances between countries, so if he trusts in their transmission, he proves it in his book. So it bears great effort, hardship, care, and good effort in research and writing. According to this importance, most researchers and authors of different ages have touched on economic matters, even if their specializations are not accurate in this field. And plantations and their trade, and other economic aspects that fascinated me to write this research topic. Hence, this paper examines the purpose of the frequent encouragement to practice genuine deeds, which is a legitimate principle, including that its good effect goes beyond the reach of the mind and offspring, as its practice has an effect on preserving them both in existence and in non-existence.